An Overview on Alcohol and Hypertension (International Journal of Food and Nutritional Sciences, 2022)
In recent decades alcohol use has joined others correlates of hypertension (HTN), including such obesity as well as salt intake, as a major research focus regarding HTN risk factors. In cross-sectional or prospective epidemiologic studies, higher blood pressure (BP) has consistently been found among people reporting average daily intake of three standard-sized drinks or more. Although specific processes have not been established, several aspects of the data, particularly short and medium term studies, suggest a causal link. Heavier drinking may, in fact, be the leading causes of reversible HTN, and reduction of excessive alcohol intake has an important public health function in HTN therapy. Added extra to the mechanism, unresolved issues about the alcohol-BP relationship are including whether there is a threshold dosage of drinking for association with HTN, the sequelae of alcohol-associated HTN and also the roles of interactions with gender, ethnicity, those certain lifestyle traits, drinking pattern, as well as choice of beverage.